An In-Depth Study Linking the Infrared Spectroscopy and Photoluminescence of Porous Silicon during Ambient Hydrogen Peroxide Oxidation. Issue 5 (May 2013) - Caras, Caley A.; Reynard, Justin M.; Bright, Frank V.
We carefully tailored a porous silicon (pSi) surface by oxidation with hydrogen peroxide (H2 O2 ) to determine the time-dependent changes in nano-crystallite surface chemistries (e.g., Si–O-Si, SiHx [x = 1, 2], Oy SiH [y=2, 3], and SiOH/H2 O) and their influence on the pSi photoluminescence (PL). The relationship between infrared band amplitudes and PL intensity were evaluated under H2 O2 and O3 (previously studied) oxidation. The pSi surface composition under O3 and H2 O2 oxidation conditions tended to, save the Oy SiH (y=2, 3) species, approach similar values at the longest oxidation times studied, but they took very different paths in reaching these end points. Furthermore, the pSi surface compositions that exhibit maximum/minimum PL under each oxidant are very different.